Find the equation of the tangent to the curve y = (2x -3)^3 at the point (1, - 1), giving your answer in the form y = mx + c.

y = (2x -3)^3

y = (2x)^3 + 3.((2x)^2)(-3) + 3.(2x).(-3)^2 + (-3)^2 using Pascal's Triangle.

y = 8x^3 - 36x^2 + 54x - 27 

dy/dx = 24x^2 - 72x + 54

at point (1,-1); dy/dx = 24 -72 + 54 = 6

Therefore tangent line is of the form y=6x + c

at point (1,-1); -1=6.1 + c

Therefore c = -7 and tangent line is y = 6x - 7.

Answered by Robert S. Maths tutor

11511 Views

See similar Maths A Level tutors

Related Maths A Level answers

All answers ▸

A curve has parametric equations x=t(t-1), y=4t/(1-t). The point S on the curve has parameter t=-1. Show that the tangent to the curve at S has equation x+3y+4=0.


Lorem ipsum dolor sit amet


At x=3, is the polynomial y= (4/3)x^3 -6x^2 + 11 at a maxima or minima?


Differentiate with respect to x: w=4x^2 + 3sin(2x)


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences